Rasch Model Study on Mathematics Examination Test Using Item Response Theory Approach - Futri, Vegi Intan; Rosnawati, Raden; Rahim, Abdul; Marlina, Marlina (Universitas Ahmad Dahlan, 2022)
This study was conducted to analyze the test instrument used to measure the ability of students in the odd final exam in mathematics. Sampling using purposive sampling technique. These students consist of 398 students. The questions given are in the form of multiple-choice questions with a total of 40 items. The data analysis technique used quantitative descriptive analysis. Data analysis was carried out using the Item Response Theory (IRT) Rasch model approach with the help of QUEST software. The results of the analysis show, from 40 items there are 39 items fit with the Rasch model. Judging from the level of difficulty, items with very difficult categories are 0%, difficult categories are 8 items or 21%, moderate item categories are 23 items or 59%, easy categories are 8 items or 21%, and very easy categories are 0 %. The reliability of the estimatedvalue of the item is 0.95 with a very good category so that it affects the items that fit the model. Thehigher reliability, the more items that fit the model. The reliability of the case estimate value is 0.00with a weak category. This value indicates an inconsistency in the answers of the test takers, whichmeans that the test takers are careless in answering the questions, thus affecting the reliability ofthe questions.